Effect of three-dimensional macrotexture characteristics on dynamic frictional coefficient of asphalt pavement surface - Hu, Liqun; Yun, Di; Liu, Zhuangzhuang; Du, Shaowen; Zhang, Zhen; Bao, Yingbo (Construction & building materials, 2016)
•Rebuild the 3D pavement surface images using data collected by laser scanner.•Describe characteristics of road macro-texture in detail using eight 3D parameters.•Increasing sharp-angular aggregates exposed in surface can improve skid resistance. The surface macrotexture of asphalt mixture significantly influences the skid resistance of pavement. In this study, a handy laser scanner was employed to collect (3D) macrotexture data of asphalt pavement surface, and the dynamic friction coefficient of pavement surface was measured by a dynamic friction tester. In order to qualitatively analyze the influence of macrotexture on the skid resistance, the 3D images of macrotexture were re-constructed based on the measured data, eight different parameters were used to describe the 3D characteristics of macrotexture images. Furthermore, the influence of these parameters on dynamic friction coefficient was analyzed by statistic methods. The results show that the relationship between mean profile depth and friction coefficient at different test speed is not close as expected. The peak density and the arithmetic mean peak curvature of 3D macrotexture images have significant positive influence on the dynamic friction coefficient. However, the effect of these two factors on the friction coefficient depends on the test speed. The study recommends improving the skid resistance of asphalt pavement by increasing the number of aggregates exposed in pavement surface and using sharp-angular aggregate.